2009
DOI: 10.1212/01.wnl.0000345010.98495.fc
|View full text |Cite
|
Sign up to set email alerts
|

Do the unintended actions of botulinum toxin at distant sites have clinical implications?

Abstract: Over the past 2 decades, botulinum toxin (BT) has enjoyed phenomenal success as a safe and effective therapeutic tool for neurologic and non-neurologic conditions. Even though recent evidence-based conclusions are limited by the availability of data, clinicians' practice confidently recommends BT for many clinical conditions. Besides being effective, BT injected locally has also been considered safe, because no evidence showed that the toxin acts also at distant sites. Recent findings from basic scientific res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 52 publications
1
44
1
1
Order By: Relevance
“…These adverse events may be fatal if left untreated. Additionally, experimental studies in rodents have shown that botulinum toxin receptors exist in the central nervous system and a small amount of botulinum toxin crosses the blood-brain barrier [53]. This raises the possibility that botulinum toxin is transported retrogradely, similar to tetanus toxin, and may cause centrally mediated side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse events may be fatal if left untreated. Additionally, experimental studies in rodents have shown that botulinum toxin receptors exist in the central nervous system and a small amount of botulinum toxin crosses the blood-brain barrier [53]. This raises the possibility that botulinum toxin is transported retrogradely, similar to tetanus toxin, and may cause centrally mediated side effects.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, these findings raise the question whether BTX-A injected into muscles or cutis might induce unexpected central actions, and whether these actions might have clinical relevance (Currà and Berardelli, 2009). …”
Section: Evidence Of An Axonal Transport Of Btx-amentioning
confidence: 99%
“…Also, studies in humans support the idea that BTX-A injected at therapeutic doses induces distant spinal and cortical effects indirectly by promoting brain changes due to plastic rearrangements subsequent to denervation or alterations in sensory input [22]. An excellent clinical example is that BTX injected into the affected muscles in patients with cervical dystonia relieves pain [10]. In addition, possible direct central actions mediated through toxin axonal transport from periphery to the spinal cord ventral horn have been reported in patients treated for spasticity [26].…”
Section: Discussionmentioning
confidence: 98%
“…Although differing in clinical manifestation, the fundamental mode of action -inhibition of neurotransmission -is common to all Clostridium neurotoxins [5,33,44]. In vitro and in vivo animal studies show that BTX alters acetylcholine, glutamate, noradrenaline, serotonin, dopamine, and glycine transmission, and may change the electrophysiologic properties, differentiation, and survival of central neurons [10]. Inhibition of neurotransmitter release by BTX is caused by the specific cleavage of a group of proteins integral to the exocytotic process, the SNARE proteins (soluble NSF-attachment protein receptors).…”
Section: Introductionmentioning
confidence: 99%